Responsibility of The Sidenreng Rappang Religious Court Class IB Based on Maqāṣid Al-Sharīʻah in Reducing The Rate of Marriage Dispensation - Astuti, Tri; Rahmawati, Rahmawati; Said, Zainal; Basri, Rusdaya; Yunus, Mukhtar (Jurnal Indonesia Sosial Sains, 2024)
This research aims to evaluate the responsibility of Sidenreng Rappang Class IB Religious Court in reducing the number of marriage dispensations. The study employs a qualitative approach with a case study method, involving in-depth interviews with judges, court officials, as well as families and couples applying for marriage dispensation. The findings of the study are as follows: 1) From 2019 to 2023, there has been a significant shift in the number of marriage dispensation applications at Sidenreng Rappang Class IB Religious Court. This shift indicates a change in societal perspectives on marriage values and the challenges they face in meeting marriage requirements. 2) Factors such as changes in family structure, increased social mobility, and the evolution of religious and cultural norms may contribute to this trend. Additionally, difficulties in meeting marriage requirements can drive individuals to seek dispensation. 3) The responsibility of Sidenreng Rappang Class IB Religious Court is also critical in preventing child marriages. The court's role includes tightening the examination of administrative requirements, providing explanations, exploring the genuine intentions of the child, and considering the true benefits and harms of child marriage